We know the derivative of e^{x}, which is e^{x}.
(e^{x})' = e^{x}
We can find the derivative of e^{tan√x} using chain rule.
Find ᵈʸ⁄dₓ, if
y = e^{tan√x}
Let u = √x.
y = e^{tan}^{u}
Let v = tanu.
y = e^{v}
Now,
y = e^{v} ----> y is a function of v
v = tanu ----> v is is a function of u
u = √x ----> u is is a function of x
By chain rule, the derivative of y with respect to x :
Substitute y = e^{v}, v = tanu and u = √x.
Substitute v = tanu.
Substitute u = √x.
Therefore,
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
Mar 01, 24 10:45 PM
Mar 01, 24 08:48 PM
Mar 01, 24 08:12 AM